(untitled) (Research, Society and Development, 2021)
The work in question aims to carry out an approach about the historical and cultural heritage, in a generic way, passing, later, to the analysis of the Monument to Christ the Redeemer, located in the city of Itaporanga, in Paraíba. In this perspective, this study, through exploratory research, of qualitative nature, deductive method, collection of bibliographic and documentary data, proceeded in order to carry out an analysis about the importance of national historical and cultural heritage, associating it to the need their preservation, through the performance of public administration at national, state and municipal levels. In this sense, we sought to highlight the origins and histories that guide the referred local heritage, which justify the need for preservation, which is an attribution of the Union, the State and the Municipality, with the collaboration of society. Finally, in view of the exposed problem, it was sought, based on the dictates that govern the Constitutional Charter, to elucidate the need for Public Administration, based on the defense of culture and national history, to seek to act in face of this duty to protect the national historical-cultural heritage.